Lactic acid bacteria in the brewing of traditional Daqu liquor - Zhao, Qing‐Song; Yang, Jian‐Gang; Zhang, Kai‐Zheng; Wang, Ming‐Yao; Zhao, Xing‐Xiu; Su, Chang; Cao, Xin‐Zhi (Journal of the Institute of Brewing, 2020)
Lactic acid bacteria and their metabolites play important roles in defining Chinese liquor flavour. Currently, the role of lactic acid bacteria in liquor brewing remains unclear. This review discusses the role of lactic acid bacteria in fermentation of different types of Daqu and fermented grains. It focuses on the interaction between these bacteria and other microorganisms during liquor brewing, and analyses its effect on liquor flavour and quality. In addition, the roles of Lactobacillus in reducing the amount of unfavourable ingredients in liquor and the succession law of lactic acid bacteria during the fermentation of three Daqu liquors were also studied. Finally, the methods aimed at reducing lactic acid production and improving liquor quality are discussed. Overall, the review highlights the significance of lactic acid bacteria for brewing Daqu liquor. Nevertheless, further studies are required to clarify the role and mechanism of action of lactic acid bacteria during liquor fermentation. © 2019 The Institute of Brewing & Distilling